Noncardiac anomalies in children with congenital heart disease - Huang, Xianghui; Gao, Yuan; Chen, Weicheng; Sheng, Wei; Huang, Guoying (Frontiers in Cardiovascular Medicine, 2023)
Objective: noncardiac anomalies (NCAs) in patients with congenital heart defect (CHD) is crucial for perioperative management and etiology studies. This study aimed to investigate NCAs in Chinese children with CHD.To explore the relationship between CHD types and noncardiac malformations and genetic rules to provide evidence for the prevention and treatment of birth defects. Methods: Medical records for 3,776 CHD-diagnosed children hospitalized hospitalized from 1 January 2015 to 31 December 2019 were collected and subjected to retrospective analyses to excavate potential association rules between CHDs, and noncardiac malformations, and chromosome results. Results: The main types of CHD are left-to-right shunts (67.61%), followed by right-to-left shunts (26.54%). The probability of noncardiac malformation is not all equal in the (P＜0.0001) three classifications of CHD, the incidence of NCA from right-to-left CHD higher than left-to-right and non-shunt (without sling and heterotopia). There was a notably high co-occurrence of cardiac looping defects with laterality defects.In addition, 39.58% of children had chromosome abnormalities. Moreover, there was a significant difference in the probability of chromosomal abnormality between CHD with and without noncardiac This is a provisional file, not the final typeset article malformations (P＜0.01). 3788 CHD patients were included in this study. The main phenotypes of CHD were Ventricular Septal Defect (VSD, 33.69%), Atrial Septal Defect (ASD, 12.72%), and Tetralogy of Fallot (TOF, 5.54%). A total of 887 (23.42%) cases had noncardiac anomalies, mainly associated with central nervous system (34.61%), nose/ear/mandibular/face (19.39%), genitourinary system (15.78%), and musculoskeletal system (15.56%). Compared to other CHD subtypes, septal defects had a lower percentage of associated NCAs (P=3.7e-09) while AVSD had a higher percentage (P=0.0018). Conclusions: NCAs are prevalent among CHD-diagnosed children in China and . the spectrums of NCAs in different CHD subcategories were different.Routine screening and chromosome testing of noncardiac systems is indispensable, especially CHD occurring with hemodynamic changes.